2005
DOI: 10.1124/mol.105.013474
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K3 (Menadione)-Induced Oncosis Associated with Keratin 8 Phosphorylation and Histone H3 Arylation

Abstract: The vitamin K analog menadione (K3), capable of both redox cycling and arylating nucleophilic substrates by Michael addition, has been extensively studied as a model stress-inducing quinone in both cell culture and animal model systems. Exposure of keratin 8 (k-8) expressing human breast cancer cells (MCF7, T47D, SKBr3) to K3 (50 -100 M) induced rapid, sustained, and site-specific k-8 serine phosphorylation (pSer73) dependent on signaling by a single mitogen activated protein kinase (MAPK) pathway, MEK1/2. Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…In the past, studying an endothelial cell death model, Chang et al [29] suggested that the protective effect of GSH could be explained by its capacity to conjugate with menadione outside of the cell and reduce the cellular uptake of the unconjugated form of the quinone. By using GSH as a thiol donor in an in vitro acellular fluorometric assay [28], we confirmed that the formation of conjugates between menadione and GSH led to the appearance of a fluorescent arylation product (Figure 6). Thus, fluorescence spectra analysis revealed that the addition of menadione to the GSH solution sufficed to generate a fluorescence that was undetectable with menadione or GSH alone (Figure 6).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In the past, studying an endothelial cell death model, Chang et al [29] suggested that the protective effect of GSH could be explained by its capacity to conjugate with menadione outside of the cell and reduce the cellular uptake of the unconjugated form of the quinone. By using GSH as a thiol donor in an in vitro acellular fluorometric assay [28], we confirmed that the formation of conjugates between menadione and GSH led to the appearance of a fluorescent arylation product (Figure 6). Thus, fluorescence spectra analysis revealed that the addition of menadione to the GSH solution sufficed to generate a fluorescence that was undetectable with menadione or GSH alone (Figure 6).…”
Section: Resultsmentioning
confidence: 58%
“…Both GSH depletion and the menadione-induced fluorescence are facilitated by the expression of AIF. This kind of menadione-induced fluorescence has been reported to result from the arylation of cellular proteins including nuclear histones [27, 28]. One argument in favor of this possibility is the observation that exogenous GSH, which is not cell membrane-permeable (contrary to its ethyl ester that enters cells), protected cells from the cytotoxic effect of menadione and abolished the fluorescent signal (Figure 5C and 5D).…”
Section: Resultsmentioning
confidence: 66%
“…Zheng et al [14] irradiated cylindromatous SACC-83 cells in vitro with different doses (2,5,10,15,20,25,30 Gy) of X-ray. They found cellular apoptosis at 2-15 Gy and obvious necrosis at more than 15 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [20][21][22][23] have shown that treatment through inducing oncotic necrosis of tumor cells can effectively control tumors, if apoptosis process has been inhibited. Oncosis is an important factor in the process of tumor occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, recent studies indicate that such non-arylating vitamin K quinones can potentially activate intracellular cell growth and survival signals by their γ-carboxyglutamic acid modification of receptor ligands and membrane lipoproteins (Saxena et al, 2001). We have been exploring the cellular and subcellular consequences of short-term (≤8 h) exposure to the redox-cycling and arylating K3 quinone on both hormone-independent (ER-negative SKBr3) and hormone-dependent (ER-positive MCF7 and T47D) cell line models of the human breast (Liang et al, 1998;Scott et al, 2005).…”
Section: Quinone Effects On Hormone-independent Pathwaysmentioning
confidence: 99%